Male buffalo calf rearing A means to boost rural economy - Kaushik, Purushottam; Kumar, Pankaj; Dayal, Shanker (Indian Farming, 2016)
Buffaloes in India are a source of raw material like raw hides, skins and semi finished leathers for the leather industry. Male buffalo calf is specially reared for meat production and supply of skin and hides to leather industries.